2001
DOI: 10.1063/1.1370539
|View full text |Cite
|
Sign up to set email alerts
|

HgCdTe photodetectors with negative luminescent efficiencies >80%

Abstract: We have characterized the negative luminescent properties of photovoltaic HgCdTe detector structures with a room-temperature cutoff of 4.2 μm. Using an optical modulation method to directly measure the emittance as a function of applied bias and temperature, the blackbody signal at 295 K is found to be suppressed by a factor of 5.6. The negative luminescence efficiency of 82% and the apparent blackbody temperature change of ≈−35 K are nearly independent of heatsink temperature over the range 265–305 K.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2003
2003
2006
2006

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 7 publications
1
16
0
Order By: Relevance
“…The emittance was measured as a function of temperature, using a self-referenced optical modulation technique. 4 Since the biased device is referenced to the same device unbiased, the measurement does not depend on knowing the collection efficiency, sample reflectivity, or active area. It is, however, critical that only the active device be imaged onto the detector, and hence, the image is magnified tenfold Midwave-Infrared Negative Luminescence Properties of HgCdTe Devices on Silicon Substrates 653 Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The emittance was measured as a function of temperature, using a self-referenced optical modulation technique. 4 Since the biased device is referenced to the same device unbiased, the measurement does not depend on knowing the collection efficiency, sample reflectivity, or active area. It is, however, critical that only the active device be imaged onto the detector, and hence, the image is magnified tenfold Midwave-Infrared Negative Luminescence Properties of HgCdTe Devices on Silicon Substrates 653 Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This agrees with previous findings of a MA) that displayed internal negative luminescence efficiencies (NLE) up to 82%, meaning that the blackbody emission from within the sample was reduced by over a factor of 5. 4 Those devices operated at a saturation reverse bias current density (j sat ) of ≈5 A/cm 2 . Matveev et al 10 reported slightly higher NLE (90%) for InAsSb devices ( co ≈ 6 m), but with j sat > 20 A/cm 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, NL has been observed in a number of IR detector and LED material systems with cutoff wavelengths (l co ) beyond 4 mm, including InSb, 3,6 InSb/ InAlSb heterostructures, 7,8 InAs,9 In(Ga)As(Sb)/ InAsSb(P) heterostructures, 10-18 type-II InAs/GaSb superlattices, 19 and HgCdTe. 4,5,8,[20][21][22][23][24][25][26][27][28][29][30] The best NL device performance to date has been obtained using relatively mature HgCdTe photodiode materials.…”
Section: Introductionmentioning
confidence: 99%
“…However, several recent studies have demonstrated substantial progress toward the development of a practical NL technology. [8][9][10][11][12][13][14][15] For example, despite having a much longer cutoff wavelength than any earlier NL structures, the HgCdTe photodiodes of Ashley et al 8 (λ co Ͼ 8 µm) displayed j sat of only 4.5 A/cm 2 . 11 Matveev et al 10 reported a very high NL efficiency (90%) for InAsSb devices (λ co Ϸ 6 µm), although j sat was 20 A/cm 2 .…”
Section: Introductionmentioning
confidence: 99%